Wrestling with God : finding hope and meaning in our daily struggles to be human - Rolheiser, Ronald (New York : Image Books, 2018)
In Wrestling with God, Ronald Rolheiser helps us avow and understand our faith in a world where nothing seems solid or permanent. Drawing from his own life experience, as well as a storehouse of literary, psychological, and theological insights, the author of Sacred Fire examines the fears and doubts that challenge us.
Wrestling for self-understanding within a complex nature -- Wrestling with our erotic energies -- Wrestling with fear -- Wrestling with the Gospel mandate to reach out to the poor -- Wrestling with faith and doubt -- Wrestling with God -- Wrestling for faith within a complex culture -- Some guidelines for the long haul.
Includes an excerpt from the author's Sacred fire.
Keywords: Catholic Church -- Theology; Faith; Belief and doubt; Spiritual life -- Christianity